A contribuição do conceito do bit quântico(q-bit) para os fundamentos teóricos da ciência da informação - Pimentel Sobrinho, Alvaro Caetano (2013)
Study about contributions of the concept of quantum bit (q-bit) and analyze the possibilities in quantum computers processing and increase the data storage capacity for devices memory. From the analysis of the q-bit is possible to notice changing in mental and social structures beyond their direct interference in the process of memory as a way of preserving information in different formats. Observations in the contributions from Quantum Mechanics, by measuring process, for Information Science and theoretical-epistemic confluence between the two sciences complemented by some opinions around the issues that still needing answer. Insertion of terms entanglement and superposition that were identified as fundamental to understanding the concept of q-bit is the basis to accept the updates in the concepts, formulations and descriptions established in Information Science